Bibliometric analysis of martial arts monographs published in Spain (1906-2006) (Revista de Artes Marciales Asiáticas, 2012)
This paper examines the martial arts monographs published in Spain between 1906 and 2006 from a bibliometric point of view. Starting from Pérez and Gutiérrez’s previous bibliography (2008), the total number of published monographs following the criteria of subject, decade and the combination of both was analyzed. The results showed a total of 2.036 books (1.285 original editions) with a prevalence of Japanese and Chinese martial arts. A group of eight subjects exceeded a hundred volumes (karate, judo/jujutsu, taijiquan, wu-shu/kung fu, classics, qigong, philosophy, history and education, and aikido), with two patterns of bibliographic evolution appearing. The first, represented by Japanese martial arts considered as a group and martial arts focused on the utilitarian and/or sporting performance aspects (judo/jujutsu, karate and wu-shu/kung fu), developed increasingly until the 80’s when it followed a steady-state and/or drop. The second model, which characterises the Chinese martial arts group and martial arts mainly focused on healthy and/or spiritual aspects of training (taijiquan, qigong, aikido), has increased significantly from the 90’s until the present moment. The interpretation of these patterns and the evolution of the martial arts bibliographic production in Spain highlights some aspects such as the development of the Spanish society and sports practice, bibliographic production, reading habits, or the cultural influences of eastern countries on Spain.